1994
DOI: 10.1111/j.1365-2265.1994.tb02552.x
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in active acromegaly during treatment with octreotide: a double‐blind, placebo‐controlled cross‐over study

Abstract: Short-term octreotide therapy reduces growth hormone levels leading to a significant reduction in lean body mass as assessed by dual-energy X-ray absorptiometry. Alterations in lean body mass were positively correlated with reductions in foot volume. Thus, simple clinical tests may be valuable in judging the effects of treatment in active acromegaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…46 Furthermore, if another mechanism other than insulin suppression was responsible for the weight loss, subjects receiving octreotide for acromegaly or other disorders would be expected to lose weight and fat mass; indeed long-term octreotide usage has minimal effects on these parameters. 47 We found that insulin suppression for 24 weeks was associated with marked weight loss (mean 12.6 kg) in 18% of an otherwise healthy subpopulation of adult obese subjects, and a small but significant weight loss (mean 3.6 kg) in another 57%. This weight loss occurred without dietary or exercise intervention, and occurred slowly but without asymptote.…”
Section: Discussionmentioning
confidence: 97%
“…46 Furthermore, if another mechanism other than insulin suppression was responsible for the weight loss, subjects receiving octreotide for acromegaly or other disorders would be expected to lose weight and fat mass; indeed long-term octreotide usage has minimal effects on these parameters. 47 We found that insulin suppression for 24 weeks was associated with marked weight loss (mean 12.6 kg) in 18% of an otherwise healthy subpopulation of adult obese subjects, and a small but significant weight loss (mean 3.6 kg) in another 57%. This weight loss occurred without dietary or exercise intervention, and occurred slowly but without asymptote.…”
Section: Discussionmentioning
confidence: 97%
“…In most studies, an increase in LBM is found in active acromegaly, but again no gender differences have been reported (1,6,7,9,31). GH hypersecretion has clear anabolic effects on protein synthesis in acromegaly.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that GH excess causes marked expansion of extracellular fluid volume, reduction in body FM, and increases LBM and BMD (6)(7)(8)(9)(16)(17)(18)(19)(20). In both genders, when serum GH and IGF1 decrease after treatment, body weight falls over the first weeks due to a decrease in total body water, body cell mass, and LBM (3,4,6,16). But in most of the studies, body weight returned to previous ranges, due to an increase in body FM, 3 months after hormonal normalization (3,4,14,16,18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations